Integration of Extracurricular Programs and Student Achievement Development at SMA Muhammadiyah 1 Klaten - Adiliya Mustika Rahayu; Chusniatun Chusniatun (SAINTIS Publishing, 2025)
This research is a field research with the title “Integration of Extracurricular Programs and Student Achievement Coaching at SMA Muhammadiyah 1 Klaten” which aims to find out how the implementation and results of the integration of extracurricular programs and achievement coaching and what are the supporting and inhibiting factors. The research method used is qualitative research with a descriptive approach. The results of the research conducted are known to be the concept of implementing the integration of extracurricular programs and fostering student achievement carried out at SMA Muhammadiyah 1 Klaten which aims to provide a forum for talent interests according to what students have, and can produce knowledgeable and morally good students in accordance with the Qur'an and As-sunnah through extracurricular activities at school. It is also known that the supporting factors are in the form of support from school residents, adequate SARPRAS and cooperation between parents and teachers, then the inhibiting factor is the lack of student interest in participating in extracurricular activities and a solution is found, namely by means of extracurricular counseling by the school.category.